Beta-Blockers and mortality in patients with malignancy and cardiovascular disease: an analysis of the MIMIC-IV database - Bing-ao Chen; Sheng Lu; Qi-hang Yang; Hong-bao Chen; Yang Yuan (BMC Cancer)
Abstract Objective To evaluate the impact of β-blockers on 28-day and 180-day mortality in ICU patients with malignancies and to assess their effects on tumor-related biomarkers. Methods This study utilized data from the MIMIC-IV database. A doubly robust estimation approach combining propensity score matching (PSM) and inverse probability of treatment weighting (IPTW) was employed to compare mortality outcomes between patients who received β-blockers and those who did not. Results β-blocker use was significantly associated with reduced 28-day (adjusted OR = 0.61, 95% CI: 0.48–0.78, p < 0.001) and 180-day mortality (adjusted OR = 0.69, 95% CI: 0.59–0.84, p < 0.001). Sensitivity analyses confirmed the robustness of these findings. Among the tumor-related biomarkers analyzed, no significant changes were observed in CEA, AFP, CA-125, LDH, or WBC levels, while CRP levels showed a significant decrease. Conclusion β-blockers are associated with a significant reduction in both short-term and long-term mortality in ICU patients with malignancies. However, they appear to have limited effects on tumor-specific biomarkers, with the exception of a potential anti-inflammatory effect reflected by reduced CRP levels.